2017
DOI: 10.1007/s12072-017-9807-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of etiological treatment on prognosis

Abstract: Portal hypertension (PHT) is a frequent and severe complication of cirrhosis. PHT may lead to the development of various complications with high mortality. Liver transplantation is the gold standard as a surgical curative treatment for end-stage liver disease. Theoretically, etiological treatment focusing on the pathophysiology of the underlying disease should be the objective of the nonsurgical management of cirrhotic PHT. Chronic viral hepatitis is the major etiology of cirrhosis and PHT. In cirrhotic patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 110 publications
0
11
0
Order By: Relevance
“…Well tolerated therapies for CHC with cure rates above 95% are now available [3]. Treatment leading to sustained virological response (SVR) is associated with decrease in liver stiffness [4, 5] and a reduction in the risk of progressing to cirrhosis, HCC and end-stage liver disease [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Well tolerated therapies for CHC with cure rates above 95% are now available [3]. Treatment leading to sustained virological response (SVR) is associated with decrease in liver stiffness [4, 5] and a reduction in the risk of progressing to cirrhosis, HCC and end-stage liver disease [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Other patients with a clear cause of HCC have the advantage of prognosis, which indicates that HCC patients could prolong their OS after accepting treatments based on disease etiology. Many reports have shown that treatments based on etiology are beneficial to improve HCC patients’ prognosis 30–34 . In order to identify the prognostic value of the constructed model, we tested an internal cohort, and the results were consistent with those of the primary cohort.…”
Section: Discussionmentioning
confidence: 72%
“…Many reports have shown that treatments based on etiology are beneficial to improve HCC patients' prognosis. [30][31][32][33][34] In order to identify the prognostic value of the constructed model, we tested an internal cohort, and the results were consistent with those of the primary cohort. Furthermore, even when we divided the whole cohort into a 2:1 ratio, as for training and validation, the results were indistinguishable (data not shown).…”
Section: Discussionmentioning
confidence: 89%
“…Similarly, the results of the present study demonstrated this point that CSPH was associated with increases in mortality of 1.97-fold. More and more evidence has suggested that antiviral therapies could reduce hepatic venous pressure gradient but these effects were limited to those with earlier stage of liver cirrhosis [32,33]. The presence of CSPH in patients with early stage HCC may imply the consideration of liver transplantation before recurrence.…”
Section: Discussionmentioning
confidence: 99%